1990
DOI: 10.1017/s0022029900029496
|View full text |Cite
|
Sign up to set email alerts
|

Yield and composition of milk from lactating mares: effect of lactation stage and individual differences

Abstract: The yields and composition of milk from nursing mares were studied during the first two months of lactation in 11 mares of heavy breeds (784 kg). Daily yield increased from 21-7 to 24-6 kg between weeks 1 and 8 of lactation. Fat, protein, gross energy and Ca concentrations significantly decreased when lactose content increased during this period. Individual variations were higher for yield than for composition. Casein, whey protein and non-protein N (56, 34 and 10% of crude protein, respectively) and amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
0
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 13 publications
8
24
0
8
Order By: Relevance
“…Non-protein N decrease of the milk from the early lactation phases (day 4 to day 60) was in substantial agreement with those observed by other authors (Doreau et al 1990;Martin et al 1992;Csapó-Kiss et al 1995). Other studies found no significant variations (Oftedal et al 1983;Oftedal and Jenness 1988) or an irregular trend.…”
Section: Discussion Nitrogen Composition Of Mare's Milksupporting
confidence: 92%
See 2 more Smart Citations
“…Non-protein N decrease of the milk from the early lactation phases (day 4 to day 60) was in substantial agreement with those observed by other authors (Doreau et al 1990;Martin et al 1992;Csapó-Kiss et al 1995). Other studies found no significant variations (Oftedal et al 1983;Oftedal and Jenness 1988) or an irregular trend.…”
Section: Discussion Nitrogen Composition Of Mare's Milksupporting
confidence: 92%
“…The same trends were observed in other breeds and/or for shorter lactation periods (Neseni et al 1958;Bowman and van der Schee 1978;Gibbs et al 1982;Oftedal and Jenness 1988;Doreau et al 1990;Smolders et al 1990;Mariani et al 1993;Csapó-Kiss et al 1995). Concerning the casein N content variations, Storch (1985) reported an irregular non-significant trend, probably because in this case he considered bulk mare's milk, and the lactation stage was not clearly defined.…”
Section: Discussion Nitrogen Composition Of Mare's Milksupporting
confidence: 58%
See 1 more Smart Citation
“…The average intake of 13.7 g/d presented in Table 2 was deemed, therefore, to be suitable for weanlings, and involved no detrimental effects. On the other hand, the methionine content of mare's milk is low (Pelfonen et al 1980;Doreau et al .1990), and methionine can not be suggested to be a limiting amino acid for growing horses. Data on other amino acids in foals are inadequate to establish any accurate recommendations.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Data on other amino acids in foals are inadequate to establish any accurate recommendations. However, data concerning the intakes and blood levels of these amino acids fl-ab, 2) may be indicative in this respect, The intakes of nine essential amino acids by weanlings (250 kg) at the end of nursing period can be calculated, assuming a milk production of 10 kg with a protein content 1 ,B-1 .9% (Grbbs et al,'1982;Burns et al 1992), and the amino acid contents reported by Peltonen et al, (1980) and Doreau et al (1990) at the end of lactation, as well as feed intake of foals as given by DLG (1984) andiVRC (1989), and using the amino acid contents given for typical solid feeds. E.9., the calculated lysine intake, approximately 35 g/d with 13,5 g of it obtained from the milk, corresponds to the range of recommended levels for weanling foals.…”
Section: Amino Acidsmentioning
confidence: 99%